High perennial ryegrass seeding rates do not negatively impact pasture sward persistence. (26th October 2017) - Lee, J. M.; Thom, E. R.; Chapman, D. F.; Wynn, K.; Waugh, D.; Rossi, L.; Faville, M. J.; Bell, N. L.; McNeill, M. R.
Abstract: Poor persistence of perennial ryegrass swards is a common problem; however, there is a lack of long‐term studies to understand the mechanisms associated with poor persistence. This study describes an experiment to test the hypothesis that high ryegrass seeding rates (>18 kg seed per ha) reduce long‐term population persistence because of smaller plant size and poorer survival during the first year after sowing. Four cultivars, representing four functional types of perennial ryegrass, were sown at five seeding rates (equivalent to 6, 12, 18, 24 and 30 kg seed per ha) with white clover in three regions of New Zealand. Swards were monitored for 5 years. No evidence was found to indicate a lack of persistence of ryegrass‐based swards sown at higher seeding rates. During the first year, swards sown at higher seeding rates had greater herbage accumulation (except at the Waikato site), greater ryegrass tiller density and greater ryegrass content. This initial impact of high seeding rates had largely dissipated by the fourth year, resulting in swards with similar annual herbage accumulation, tiller density and botanical composition. Similarly, there were relatively few differences among cultivars for these variables. Although high seeding rates did not negatively impact sward persistence, geographical location did, with strong evidence of ryegrass population decline at the Waikato site for all treatment combinations, some decline in Northland, and stable populations in Canterbury. It is possible that productive perennial ryegrass pastures can only be sustained for 4–5 years in some situations, even when the best ryegrass technology and management practices are used.